2013
DOI: 10.1128/mcb.01342-12
|View full text |Cite
|
Sign up to set email alerts
|

DCNL1 Functions as a Substrate Sensor and Activator of Cullin 2-RING Ligase

Abstract: Substrate engagement by F-box proteins promotes NEDD8 modification of cullins, which is necessary for the activation of cullin-RING E3 ubiquitin ligases (CRLs). However, the mechanism by which substrate recruitment triggers cullin neddylation remains unclear. Here, we identify DCNL1 (defective in cullin neddylation 1-like 1) as a component of CRL2 called ECV (elongins BC/CUL2/VHL) and show that molecular suppression of DCNL1 attenuates CUL2 neddylation. DCNL1 via its DAD patch binds to CUL2 but is also able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…This suggests that binding of the substrate adaptor to the SCCRO-cullin-ROC1 complex is required to promote neddylation. Heir et al reported that binding of substrate (HIF1␣) to the substrate receptor von Hippel-Lindau (VHL) promotes binding of SCCRO to VHL and cullin (Cul2) (39). This led to the suggestion that SCCRO functions as a "substrate sensor switch," with binding of substrate to SCCRO via the substrate adaptor being required to trigger cullin neddylation.…”
Section: Sccro Selectively Regulates Neddylationmentioning
confidence: 99%
“…This suggests that binding of the substrate adaptor to the SCCRO-cullin-ROC1 complex is required to promote neddylation. Heir et al reported that binding of substrate (HIF1␣) to the substrate receptor von Hippel-Lindau (VHL) promotes binding of SCCRO to VHL and cullin (Cul2) (39). This led to the suggestion that SCCRO functions as a "substrate sensor switch," with binding of substrate to SCCRO via the substrate adaptor being required to trigger cullin neddylation.…”
Section: Sccro Selectively Regulates Neddylationmentioning
confidence: 99%
“…Neddylation of cullins promotes assembly of the CRL complex and optimizes its conformation to allow efficient transfer of ubiquitin from the E2 to the substrate protein. In its role in promoting neddylation, SCCRO activity regulates levels of ubiquitination activity in cells: an increase in SCCRO activity increases levels of ubiquitinated proteins by promoting CRL activity, whereas a decrease in SCCRO activity has the opposite effect (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…7 E), indicating that less HIF1α is recruited to VHL in the presence of p62. Because conjugation of Nedd8 to CUL2 (neddylation) is crucial for activation of CUL2, and the engagement of the substrate HIF1α with VHL prompts DCNL1 recruitment and then initiates CUL2 neddylation ( Heir et al, 2013 ), we studied whether p62 regulates CUL2 neddylation. Co-immunoprecipitation assays showed that p62 inhibited the DCNL1–CUL2 interaction in a dose-dependent manner ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that CUL2 neddylation is important for its E3 ligase activity. DCNL1 mediates CUL2 neddylation upon engagement with HIF1α ( Heir et al, 2013 ). We provide the first evidence that p62 binds to and inhibits the activity of VHL ubiquitin ligase by inhibiting CUL2 neddylation.…”
Section: Discussionmentioning
confidence: 99%